An ethnobotanical study of anti-malarial plants among indigenous people on the upper Negro River in the Brazilian Amazon - Frausin, Gina; Hidalgo, Ari de Freitas; Lima, Renata Braga Souza; Kinupp, Valdely Ferreira; Ming, Lin Chau [UNESP]; Pohlit, Adrian Martin; Milliken, William (Elsevier B. V., 2015)
In this article we present the plants used for the treatment of malaria and associated symptoms in Santa Isabel do Rio Negro in the Brazilian Amazon. The region has important biological and cultural diversities including more than twenty indigenous ethnic groups and a strong history in traditional medicine. The aims of this study are to survey information in the Baniwa, Baré, Desana, Piratapuia, Tariana, Tukano, Tuyuca, Yanomami ethnic communities and among caboclos (mixed-ethnicity) on: a) plant species used for the treatment of malaria and associated symptoms; b) dosage forms and c) distribution of these anti-malarial plants in the Amazon. Information was obtained through classical ethnobotanical and ethnopharmacological methods from interviews with 146 informants in Santa Isabel municipality on the upper Negro River, Brazil. Fifty-five mainly native neotropical plant species from 34 families were in use. The detailed uses of these plants were documented. The result was 187 records (64.4%) of plants for the specific treatment of malaria, 51 records (17.5%) of plants used in the treatment of liver problems and 28 records (9.6%) of plants used in the control of fevers associated with malaria. Other uses described were blood fortification ('dar sangue'), headache and prophylaxis. Most of the therapeutic preparations were decoctions and infusions based on stem bark, root bark and leaves. These were administered by mouth. In some cases, remedies were prepared with up to three different plant species. Also, plants were used together with other ingredients such as insects, mammals, gunpowder and milk. This is the first study on the anti-malarial plants from this region of the Amazon. Aspidosperma spp. and Ampelozizyphus amazonicus Ducke were the most cited species in the communities surveyed. These species have experimental proof supporting their anti-malarial efficacy. The dosage of the therapeutic preparations depends on the kind of plant, quantity of plant material available, the patient's age (children and adults) and the local expert. The treatment time varies from a single dose to up to several weeks. Most anti-malarial plants are domesticated or grow spontaneously. They are grown in home gardens, open areas near the communities, clearings and secondary forests, and wild species grow in areas of seasonally flooded wetlands and terra firme (solid ground) forest, in some cases in locations that are hard to access. Traditional knowledge of plants was found to be falling into disuse presumably as a consequence of the local official health services that treat malaria in the communities using commercial drugs. Despite this, some species are used in the prevention of this disease and also in the recovery after using conventional anti-malarial drugs.
Keywords: Amerindian traditional knowledge; Ampelozizyphus amazonicus; Anti-malarial activity; Antiplasmodial activity; Aspidosperma spp.; Santa isabel do rio negro